Halometabolites isolated from the marine-derived fungi with potent pharmacological activities - Chen, Yu; Xu, Lian-Cheng; Liu, Shan; Zhang, Zi-Xiang; Cao, Guan-Yi (Frontiers in Microbiology, 2022)
Halometabolites, usually produced in marine environment, are an important group of natural halogenated compounds with rich biological functionality and drugability and thus play a crucial role in pharmaceutical and/or agricultural applications. In the exploration of novel halometabolites from marine microorganisms, the growing number of halogenated compounds makes it necessary to fully present these metabolites with diverse structures and considerable bioactivities. This review particularly focuses on the chemodiversity and bioactivities of halometabolites from marine-derived fungi. As a result, a total of 145 naturally halogenated compounds, including 118 chlorinated, 23 brominated, and four iodinated compounds, were isolated from 17 genera of marine-derived fungi. These compounds possess diverse structural types, which are classified into polyketides (62.7%), phenols (16.6%), alkaloids (14.5%), and terpenoids (6.2%). Their cytotoxic, antibacterial, and anti-inflammatory activities indicate the high potential of these halogenated compounds as lead compounds for drug discovery.